2022
DOI: 10.1186/s12889-022-13960-w
|View full text |Cite
|
Sign up to set email alerts
|

Measuring anxiety and fear of Covid-19 among older people: psychometric properties of anxiety and fear of Covid-19 scale (AMICO) in Spain

Abstract: Background The elderly population has proven to be a particularly vulnerable group with regard to the effects of the COVID-19 pandemic. The aim of this study was to study the psychometric properties of the Ansiedad y MIedo a Covid-19 scale (AMICO) on a population-based sample of elderly people. Methods A descriptive and psychometric cross-sectional study, based on questionnaires, was carried out. An exploratory and confirmatory factor analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…The exploratory factor analysis showed the maintenance of a two-factor structure with two interrelated factors: fear and anxiety underlying the data and 16 items as a result of their high factor loadings. These results offered a structure consistent with previous two-factor studies obtained from a general population by Gomez-Salgado et al ( 52 ), which explained a total variance of 64.8%, or in the case of research involving a sample of older adult people, which showed a total variance of 66.6% ( 53 ). The results of the study showed a distribution that explained a total variance of 78.935%.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The exploratory factor analysis showed the maintenance of a two-factor structure with two interrelated factors: fear and anxiety underlying the data and 16 items as a result of their high factor loadings. These results offered a structure consistent with previous two-factor studies obtained from a general population by Gomez-Salgado et al ( 52 ), which explained a total variance of 64.8%, or in the case of research involving a sample of older adult people, which showed a total variance of 66.6% ( 53 ). The results of the study showed a distribution that explained a total variance of 78.935%.…”
Section: Discussionsupporting
confidence: 90%
“…In this sense, this study provides the McDonald’s Omega coefficient (0.94) as an added reliability data, which is optimal and provides greater robustness to the reliability study of the AMICO_Pregnant instrument. Along these lines, both the study by Velez-Moron et al ( 53 ) in the validation of the AMICO scale in the older adult population and the one by Morgado-Toscano et al ( 56 ) in validating AMICO in the United Kingdom general population showed similar or slightly lower values for both Cronbach’s Alpha coefficients (0.94 and 0.96, respectively) and McDonald’s Omega coefficients (0.91 and 0.92, respectively), and very similar to the results reported by Gomez-Salgado et al ( 48 ) in the general Spanish population, which showed a Cronbach’s Alpha coefficient value of 0.92. The McDonald’s Omega coefficient was not calculated in the research by Gomez-Salgado et al ( 51 ), despite the modifications made to the wording during the design phase of the scale.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent research also demonstrated that, when applied to empirical data, McDonald's omega does not largely differ from Cronbach's alpha (Hayes and Coutts, 2020). An example in nursing seems to support this and it demonstrates the adoption of this measure in a scales' development and validation (Vélez-Morón et al, 2022). It is recommended to consider this reliability test along with Cronbach's alpha.…”
Section: Reliabilitymentioning
confidence: 93%
“…41 The reliability study gave a total Cronbach's α value of 0.92 for factor 1 (Anxiety) and of 0.90 for factor 2 (Fear). The AMICO scale has been validated in different population groups: the elderly, 42 nurses, 43 the general adult population, 44 or the general adult population in United Kingdom. 45 In this context, the scale for assessing fear and anxiety of COVID-19 in pregnant women (AMICO_Pregnant) was designed and validated in a previous study based on the Spanish version of the AMICO scale.…”
Section: Instrumentmentioning
confidence: 99%